The school is alive! - Chabert, Jack; Ricks, Sam; Branches (Scholastic Inc.) (New York : Branches/Scholastic Inc, 2014)
Sam Graves discovers that his elementary school is alive and plotting against the students, and, as hall monitor, it is his job to protect them--but he will need some help from his friends.
460
Keywords: Elementary schools -- Juvenile fiction; Best friends -- Juvenile fiction; Horror tales; Friendship -- Juvenile fiction